Sunday sparrows : selected poetry - Song, Lin, 1958- (Jintian series of contemporary literature., 2019)
Song Lin's poems explore his sojourns in several countries, the natural world outside him, and his own inner landscape. His early imprisonment during the 1989 Tienanmen Square protests gave rise to the title poem, as well as a profound sense of yearning that pervades much of his work. He is a wanderer in the world and in the language of poetry, often finding beauty in others that are also on the move: birds, rivers, the wind. While his work is rooted in both contemporary and classical Chinese poetry, he incorporates American, French, and Latin-American literary traditions into his poems.